2015
DOI: 10.1021/acs.jpcb.5b09405
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Heterodyne Transient-Grating Studies of Nonradiative Decay of the S2 (11Bu+) State of β-Carotene: Contributions from Dark Intermediates and Double-Quantum Coherences

Abstract: Femtosecond transient-grating spectroscopy with heterodyne detection was employed to characterize the nonradiative decay pathway in β-carotene from the S2 (1(1)Bu(+)) state to the S1 (2(1)Ag(-)) state in benzonitrile solution. The results indicate definitively that the S2 state populates an intermediate state, Sx, on an ultrafast time scale prior to nonradiative decay to the S1 state. Numerical simulations using the response function formalism and the multimode Brownian oscillator model were used to fit the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(82 citation statements)
references
References 78 publications
5
76
1
Order By: Relevance
“…The spectral time evolution in the sequential decay model is described by the evolutionassociated spectra (EAS). The nature of the time evolution of the EAS has been discussed in detail for β-carotene 3 and peridinin 1 in previous publications with support from a comprehensive set of numerical simulations using the response function formalism and the multimode Brownian oscillator model. Note that this work considered a range of alternative models and considered especially the possible assignment of the Sx state in peridinin to a vibrationally excited energy level of S1.…”
Section: Supporting Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The spectral time evolution in the sequential decay model is described by the evolutionassociated spectra (EAS). The nature of the time evolution of the EAS has been discussed in detail for β-carotene 3 and peridinin 1 in previous publications with support from a comprehensive set of numerical simulations using the response function formalism and the multimode Brownian oscillator model. Note that this work considered a range of alternative models and considered especially the possible assignment of the Sx state in peridinin to a vibrationally excited energy level of S1.…”
Section: Supporting Resultsmentioning
confidence: 99%
“…The experimental setup and techniques used for heterodyne transient grating spectroscopy were described in detail previously. 3 Briefly, a 250-kHz amplified Ti:sapphire laser (Coherent Mira Seed oscillator and RegA 9050 amplifier) was used to pump an optical parametric amplifier (OPA, Coherent OPA 9450).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the experimental 2D study resolves the diagonal peak due to the dark state. Furthermore, based on ultrafast-transient absorption and transient-grating experiments, some groups have suggested that the dark-state is due to a double-minima structure on the S 2 potential energy surface, not a distinct electronic state 43, 44 . This double-minima model hypothesizes that the lowest one of the S 2 potential surface minima exists at the conformation where the carotenoid is twisted from the all- trans isomer by ~90° with respect to one C=C bond of the conjugated polyene backbone.…”
Section: Discussionmentioning
confidence: 99%
“…[18] However, involvement of another dark intermediate state has also been invoked. The nature of this state, usually denoted as the S x state, is still unknown and either a separate electronic state of B u À symmetry [11,19,20] or a twisted S 2 state [21,22] have been proposed as the intermediate state facilitating the S 2 -S 1 relaxation.…”
Section: Introductionmentioning
confidence: 99%